2015
DOI: 10.1038/srep16989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacillus strains by MALDI TOF MS using geometric approach

Abstract: Microorganism identification by MALDI TOF mass-spectrometry is based on the comparison of the mass spectrum of the studied organism with those of reference strains. It is a rapid and reliable method. However, commercial databases and programs are mostly designed for identification of clinically important strains and can be used only for particular mass spectrometer models. The need for open platforms and reference databases is obvious. In this study we describe a geometric approach for microorganism identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
0
27
0
4
Order By: Relevance
“…On the contrary, the combined use of cluster analysis and the identification of biomarkers by means of the Mass‐Up and SPSS programs (Fernández‐Álvarez et al, ; López‐Fernández et al, ) allowed us grouping strains according to their taxonomic position and the typing of bacterial strains according to the intra‐ and interspecific variability of their protein spectra. Numerous studies have demonstrated that cluster analysis of MALDI‐TOF data is robust and reliable methods for discrimination of bacteria (AlMasoud, Xu, Nicolaou, & Goodacre, ; Fernández‐Álvarez et al, ; Kim et al, ; Starostin et al, ). Similarity levels of the V. salmoninarum strains tested in this study range from 87% to 92%, and eight species‐specific mass biomarkers at m/z 4,521.41, 4,845.06, 5,291.74, 6,229.97, 6,965.50, 9,043.02, 9,686.66 and 10,579.43 were detected in 100% of strains of V. salmoninarum (20 to 20 strains tested) regardless of their source of isolation or geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the combined use of cluster analysis and the identification of biomarkers by means of the Mass‐Up and SPSS programs (Fernández‐Álvarez et al, ; López‐Fernández et al, ) allowed us grouping strains according to their taxonomic position and the typing of bacterial strains according to the intra‐ and interspecific variability of their protein spectra. Numerous studies have demonstrated that cluster analysis of MALDI‐TOF data is robust and reliable methods for discrimination of bacteria (AlMasoud, Xu, Nicolaou, & Goodacre, ; Fernández‐Álvarez et al, ; Kim et al, ; Starostin et al, ). Similarity levels of the V. salmoninarum strains tested in this study range from 87% to 92%, and eight species‐specific mass biomarkers at m/z 4,521.41, 4,845.06, 5,291.74, 6,229.97, 6,965.50, 9,043.02, 9,686.66 and 10,579.43 were detected in 100% of strains of V. salmoninarum (20 to 20 strains tested) regardless of their source of isolation or geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то что в ряде работ про-демонстрирована более высокая точность идентификации с помощью МАЛДИ времяпролетной масс-спектрометрии по сравнению с секвенированием гена 16S рРНК (Rasko et al, 2005), надежная идентификация представителей Bacillus cereus group используемым методом требует нали-чия обширной и репрезентативной базы данных и про-двинутых математических методов анализа (Lasch et al, 2009). Таким образом, необходимо дальнейшее пополне-ние базы данных, созданной в ФИЦ ИЦиГ СО РАН (Starostin et al, 2015), как представителями обнаруженной группы микроорганизмов, так и другими таксонами, что позволит создать эффективный инструмент для быстрой и точной идентификации больших коллекций микроор-ганизмов, а также дифференциации микроорганизмов на внутригрупповом и внутривидовом уровне.…”
Section: Discussionunclassified
“…Кроме того, для штаммов коллекции ФИЦ ИЦиГ СО РАН проводится полногеномное секвенирование и проце-дура биотипирования на основании данных MALDI-TOF масс-спектрометрии (Bryanskaya et al, 2014;Starostin et al, 2015;Rozanov et al, 2017), а также скрининг штаммов для выявления возможности их трансформации. Выполняется поиск мобильных элементов и плазмид, пригодных для создания систем введения экзогенной ДНК в геном микро-организма; изучение системы рестрикции-модификации выбранных микроорганизмов; создание челночных векто-ров (Rozanov et al, 2014).…”
Section: Discussionunclassified
“…Suspected colonies of B. cereus were, also, confirmed by matrix assisted laser desorption/ionization‐time of flight mass spectrometry (MALDI‐TOF) technology. This technology generates characteristic mass spectral fingerprints, that are unique signatures for each microorganism (Charnot‐Katsikas, Tesic, Boonlayangoor, Bethel, & Frank, ; Starostin et al, ). All suspected colonies isolated in Tryptic soy agar medium (Biolife, Milano, Italy) with 5% sheep blood (Biolife, Milano, Italy) were mixed with 1 µl of α‐cyano‐4‐hydroxycinnamic acid (CHCA) matrix (bioMérieux, Firenze, Italy) on a conductive metal plate.…”
Section: Methodsmentioning
confidence: 99%